2019
DOI: 10.5194/tc-2019-33
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal variation of snow depth in the Northern Hemisphere from 1992 to 2016

Abstract: Abstract. Snow cover is an effective best indicator of climate change due to its effect on regional and global surface energy, water balance, hydrology, climate, and ecosystem function. We developed a long term Northern Hemisphere daily snow depth and snow water equivalent product (NHSnow) by the application of the support vector regression (SVR) snow depth retrieval algorithm to historical passive microwave sensors from 1992 to 2016. The accuracies of the snow depth product were evaluated against observed sno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Only errors in precipitation or temperature for the current month were considered in previous studies, however, it has been found that winter snow can also be affected by the precipitation and temperature of the months prior to the winter (Qiao et al., 2021). In addition, the remote sensing (Venäläinen et al., 2021; Xiao et al., 2020) and reanalysis (Bian et al., 2019; Mortimer et al., 2020; Orsolini et al., 2019) snow data may have limitations in certain conditions. For example, mountainous regions are masked out in the widely used Globsnow 3.0 SWE data set, owing to methodological limitations under complex terrains (Luojus et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Only errors in precipitation or temperature for the current month were considered in previous studies, however, it has been found that winter snow can also be affected by the precipitation and temperature of the months prior to the winter (Qiao et al., 2021). In addition, the remote sensing (Venäläinen et al., 2021; Xiao et al., 2020) and reanalysis (Bian et al., 2019; Mortimer et al., 2020; Orsolini et al., 2019) snow data may have limitations in certain conditions. For example, mountainous regions are masked out in the widely used Globsnow 3.0 SWE data set, owing to methodological limitations under complex terrains (Luojus et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…CC BY 4.0 License. application in remote sensing fields is promising (Liang et al, 2015;Bair et al, 2018;Xiao et al, 2018;Xiao et al, 2019). ML techniques can reproduce the nonlinear effects and interactions between variables without assumptions of a functional form.…”
Section: Introductionmentioning
confidence: 99%